The Application of Local Culture and Science-Based Islam Religious Education Curriculum at Schools and Madrasa - Firman Mansir (Jayapangus Press, 2023)
This research studies a pattern through the application of science and culture-based Islamic Education at schools and madrasa. This research refers to an application based on natural science related to local culture in Indonesia by giving priority to the values in Islam. This research aims to search for and research applied science by pairing or linking it with the culture of Indonesia. It is research about the application in the learning process in which the scope discusses the science of local culture by prioritizing an approach to Islamic values. In the process, this research is not directing the learning of Islamic Religious Education in the realm of qualitative and quantitative or merging, but this learning can use one or even both in the learning methodology. The results of this study explain that the application of learning that leads to science and refers to Indonesian culture by looking at Islamic values. It can be referred to as observations of habits taught and practiced in the learning Islamic Religious process activities in schools and madrasa